How to Represent Abstract Concepts? From the Perspective of Conceptual Metaphor Theory - Yanli Huang (Journal of Human Psychology, 2020)
How human understand and represent concepts is always a hot topic in cognitive psychology. According to the conceptual metaphor theory 12, understanding and representing abstract concepts rely on concrete concepts via metaphoric mappings. In this review, we discussed three core issues with the aim to have a comprehensive understanding of conceptual metaphors. First, I describe the underlying process of metaphoric mappings. Lakoff and Johnson (1999) 2 put forward that the source domain (concrete concepts) can be used to represent the target domain (abstract concepts). The metaphoric mappings from source domains to target domains are characterized as image schemas, which structure and provide sensory-motor grounding for abstract concepts. Then, I concerned on the directionality (the second issue) and automaticity (the third issue) of metaphoric mappings. According to conceptual metaphor theory, metaphoric mappings have the directionality from the concrete domain to the abstract domain, which is an automatic and obligatory process with neither effort nor awareness. However, directionality and automaticity were debated by recent research. In this article, by focusing on the three important issues I provided a comprehensive review which would help deepen our understanding about the nature of metaphoric mappings.
Keywords: Embodied Cognition